Design of Depth Classification:Methodology - Ranganathan, S. R. (Journal of Information and Knowledge, 1964)
Begins with a rapid account of the evolution of the practice and theory of classification during the last one hundred years and of the concepts and the terminology associated therewith. Then follows’ an account of the successive removal, during the last forty years, of six inhibitions in the Idea Plane in the development of CC caused by the Notational Plane and of the inhibitions in the Notational Plane itself caused by the DC tradition. Shows the greater practicability of the method of First-Link-Downwards Approach than that of the Last-Link-Upwards Approach. Recommends the, blending of the speculative method and the pragmatic method as a corrective of each other, at convenient stages, in designing a Scheme for Classification. After introducing a new and more easily applicable use of the terms ’Sector’ and ’Zone’ in the Notational Plane of CC, shows the number of true (IN) available in an array of order I to be 100 if the number of digits in an (AIN) is not to exceed 1; 400 if it is not to exceed 2; and 1,000 if it is not to exceed 3. Gives a scheme of allocation of the sectors to (WI), (̅WI), and (═WI). Lays down a procedure for determining the necessary first characteristics-that is (QI)-and determining their sequence with the aid of the Wall-Picture Principle in the design of classification. States that the Telescoping in Array made possible in this procedure satisfies the finding of the physiology of the eye and of the psychology of memory. Describes seven steps in the design of depth classification. Traces the progressive elimination of Gap Device in notation. Shows the training in the methods of applied research in the designing of classification to be essential for a documentalist as distinct from a generalist librarian.